2018
DOI: 10.1128/mbio.00938-18
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Biosafety Level 2-Approved, Multidrug-Resistant Strains of Mycobacterium tuberculosis through Nutrient Auxotrophy

Abstract: Multidrug-resistant (MDR) tuberculosis, defined as tuberculosis resistant to the two first-line drugs isoniazid and rifampin, poses a serious problem for global tuberculosis control strategies. Lack of a safe and convenient model organism hampers progress in combating the spread of MDR strains of Mycobacterium tuberculosis. We reasoned that auxotrophic MDR mutants of M. tuberculosis would provide a safe means for studying MDR M. tuberculosis without the need for a biosafety level 3 (BSL3) laboratory. Two diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 28 publications
0
33
0
Order By: Relevance
“…In addition to iron sequestration, restricted access to other metal ions such as Zn 2+ , Cu 2+ and Mn 2+ can also reduce microbial fitness and growth [48][49][50][51] . Most intracellular bacteria are auxotrophic [G] for purines, pyridines and/or amino acids [52][53][54][55] , which -coupled with the known metabolic restrictions of immune cells 56 -indicates an obvious link between host cell metabolism and the growth limitation of intracellular pathogens. In pivotal early experiments, IFNγ-induced degradation of host cell tryptophan was shown to restrict the growth of Toxoplasma gondii 57 .…”
Section: Metabolic Restriction Of Pathogensmentioning
confidence: 99%
“…In addition to iron sequestration, restricted access to other metal ions such as Zn 2+ , Cu 2+ and Mn 2+ can also reduce microbial fitness and growth [48][49][50][51] . Most intracellular bacteria are auxotrophic [G] for purines, pyridines and/or amino acids [52][53][54][55] , which -coupled with the known metabolic restrictions of immune cells 56 -indicates an obvious link between host cell metabolism and the growth limitation of intracellular pathogens. In pivotal early experiments, IFNγ-induced degradation of host cell tryptophan was shown to restrict the growth of Toxoplasma gondii 57 .…”
Section: Metabolic Restriction Of Pathogensmentioning
confidence: 99%
“…2A). One such DRM, Φ 2 DRM9, in which the expression of tdTomato is driven by the promoter of the chaperone gene dnaK , has been used to visualize persisters produced during drug treatment [87,91,92] or present in sputum samples of TB patients [87]. Time-lapse photography of M. tuberculosis cells infected with Φ 2 DRM9 on a microfluidic chip and incubated in INH-containing media revealed that the majority of cells initially displayed a greenish-yellow fluorescence (Fig.…”
Section: Detecting Inh Persister M Tuberculosis Cellsmentioning
confidence: 99%
“…Doubly auxotrophic strains include Δ lysA Δ panCD (Sambandamurthy et al, 2002, 2005) and Δ leuD Δ panCD (Sampson et al, 2004). Recent work generated a drug-susceptible and drug-resistant triple auxotrophic stain of M. tuberculosis , which provides a safe model for studying drug-resistant M. tuberculosis under BSL2 conditions (Vilchèze et al, 2018). Another interesting development is the use of a streptomycin-dependent M. tuberculosis strain ( M. tuberculosis 18b) as a model of latent TB (Zhang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%